1992
DOI: 10.1037/0012-1649.28.5.925
|View full text |Cite
|
Sign up to set email alerts
|

Parents' child-rearing style and child's sociometric status.

Abstract: This study examined relationships between parents' child-rearing style, the child's prosocial behavior, and the child's sociometric status. The sample consisted of 112 children (6-11 years of age) and both their parents. Parental behavior in the interaction with the child was observed at home when parents and child worked together in 2 structured tasks. Factor analyses of parental behavior revealed that 2 factors, Authoritative/Democratic and Authoritarian/Restrictive, can be found in the subsamples of mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
0
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 50 publications
12
94
0
6
Order By: Relevance
“…This authoritative parenting style has been shown to be linked to positive child adjustment (Kaufmann, Gesten, Lucia, Salcedo, Rendina-Gobioff, & Gadd, 2000). The same parents reported using less of the authoritarian parenting style which has been linked to negative child adjustment (Chen, Dong, & Zhou, 1997;Dekovic & Janssens, 1992;Thompson, Hollis, & Richards, 2003). Finally, the least reported parenting style used by these parents is the permissive parenting style, also associated with negative child adjustment (Williams, Degnan, Perez-Edgar, & Henderson, 2009).…”
Section: Findings and Research Literature: Partmentioning
confidence: 98%
See 1 more Smart Citation
“…This authoritative parenting style has been shown to be linked to positive child adjustment (Kaufmann, Gesten, Lucia, Salcedo, Rendina-Gobioff, & Gadd, 2000). The same parents reported using less of the authoritarian parenting style which has been linked to negative child adjustment (Chen, Dong, & Zhou, 1997;Dekovic & Janssens, 1992;Thompson, Hollis, & Richards, 2003). Finally, the least reported parenting style used by these parents is the permissive parenting style, also associated with negative child adjustment (Williams, Degnan, Perez-Edgar, & Henderson, 2009).…”
Section: Findings and Research Literature: Partmentioning
confidence: 98%
“…Authoritarian parenting has been associated with feelings of frustration, insecurity, and confusion (Chen, Dong, & Zhou, 1997), poor social competence (Dekovic & Janssens, 1992), and with a greater risk of developing conduct problems (Thompson, Hollis, & Richards, 2003). Permissive parenting has been linked to social withdrawal, anxiety, and depression in children (Williams, Degnan, Perez-Edgar, & Henderson, 2009).…”
Section: Baumrind's Parenting Stylesmentioning
confidence: 99%
“…In addition, keeping the maternal and paternal parenting dimensions in separate models allowed for the comparison of the pat- Gender, parent education (as an index of SES), and social desirability were entered on the fi rst step to statistically control for their effects. Previous research has found relations among the criterion variables (e.g., sympathy) and gender and SES (Dekovic & Janssens, 1992;Eisenberg & Lennon, 1983). Social desirability was also included as a control to reduce some of the bias variance inherent in the nature of self-report data.…”
Section: Regression Models Predicting Social Competence Self-worthmentioning
confidence: 99%
“…A experiência precoce de interacção social, na presença de um adulto sintonizado com a criança e sensível às micro-alterações das emoções e dos comportamentos, é imprescindível para o desenvolvimento da capacidade simbólica, da empatia, da ressonância emocional e da auto regulação (Dekovic & Janssens, 1992;Dishion, 1990;Feldman, 2007;Hart, DeWolfe, Wozniak, & Burts, 1992;Mize & Pettit, 1997). Os parâmetros da sintonia criam um processo de ligação interpessoal e familiar especifico a cada díade, mas permitem, em simultâneo, uma margem de imprevisibilidade onde a criatividade e a variabilidade possibilitam o desenvolvimento autónomo do relacionamento social (Feldman, 2007) preparando as bases para a posterior capacidade da criança para estabelecer relações gratificantes com os pares e relações de intimidade ao longo da sua vida.…”
Section: A Interacção Precoce E O Desenvolvimento Da Criançaunclassified